Factors predicting patient satisfaction in women with advanced breast cancer: a prospective study - Wendy W. T. Lam; Ava Kwong; Dacita Suen; Janice Tsang; Inda Soong; Tze Kok Yau; Winnie Yeo; Joyce Suen; Wing Ming Ho; Ka Yan Wong; Wing Kin Sze; Alice W. Y. Ng; et al. (BMC Cancer, 2018)
Abstract Background The present study (1) examined patient satisfaction with care over the first year following the diagnosis of advanced breast cancer and (2) tested if unmet health system and information needs, physical symptom distress, and psychological distress predicted patient satisfaction. Methods Prospective study of 213 Chinese women with advanced breast cancer assessed while awaiting or receiving initial chemotherapy (baseline), then again at 1.5-, 3-, 6-, and 12-months post-baseline. Health system and information unmet (HSI) needs, psychological distress, physical symptom distress, and patient satisfaction were assessed at baseline; patient satisfaction was reassessed at each follow-up assessment. Latent growth curve analysis assessed changes in patient satisfaction over the 12 months follow-up; hierarchical multiple regression analysis tested if baseline health system information needs, physical symptom distress, anxiety and depression predicted patient satisfaction at one-year post-baseline. Results The level of patient satisfaction was high and did not change significantly over time. Only HSI needs (β = − 0.27, p < 0.005) significantly associated with baseline patient satisfaction. Patient satisfaction at one-year post-baseline was predicted by HSI needs (β = − 0.26, p < 0.005), Anxiety (β = 0.23, p < 0.05) and Depression (β = − 0.28, p < 0.005), adjusting for the effect of baseline patient satisfaction (β = 0.22, p < 0.005). Conclusions Unmet health information needs and greater depressive symptoms at initial treatment phased predicted subsequent poorer patient satisfaction. This highlights a need to reinforce the importance of patient-centered care model in managing advanced breast cancer.